Influences of the neutrophil–HDL ratio, monocyte–HDL ratio and lymphocyte–HDL ratio on patients with acute exacerbation of chronic heart failure: Neutrophil–HDL ratio, monocyte–HDL ratio and lymphocyte–HDL ratio in CHF - Zeng, Chuixu; Xu, Wei; Liu, Guiying (Journal of Medical Biochemistry, 2026)
[Objective]: To investigate the role of the neutrophil/high-density lipoprotein cholesterol ratio (NHR), monocyte/high-density lipoprotein cholesterol ratio (MHR), and lymphocyte/high-density lipoprotein cholesterol ratio (LHR) in the diagnosis and management of patients experiencing an acute flare-up of chronic heart failure.[Methods]: The study included 386 individuals who were hospitalized to the hospital between March 2022 and September 2024 and had acute exacerbations of chronic heart failure. In order to determine if the research participants had acute renal injury, they were split into two groups: those with kidney injury and those without. Based on whether major adverse cardiovascular events (MACE) happened six months after discharge, the patients were further separated into groups with poor prognoses and those with excellent prognoses. N-terminal B-type brain natriuretic peptide (NT-proBNP), blood lipids, renal function, soluble tumor factor 2 inhibitor (sST2), and routine blood parameters were assessed 24 hours and 3 days following admission. The NHR, MHR, and LHR were calculated, and the glomerular filtration rate (eGFR) was estimated. The left ventricular ejection fraction (LVEF) was measured at 24 hours and 3 days after admission, and the occurrence of major adverse cardiovascular events (MACE) was followed up for 6 months after discharge.[Results]: The renal injury group's NHR, MHR, LHR, sST2, and NT-proBNP were higher than those of the nonrenal injury group and the favorable prognosis group, respectively, 24 hours after admission, whereas the LVEF was lower than that in the nonrenal injury group and the good prognosis group (P0.05). While the LVEF and eGFR were significantly lower than those in the nonrenal injury group and the good prognosis group, respectively. Three days following admission, NHR, MHR, LHR, sST2, NT-proBNP, BUN, and Scr were substantially higher in the renal injury group and the poor prognosis group (P
Keywords: Heart failure; Neutrophil/high-density lipoprotein cholesterol ratio; Monocyte/high-density lipoprotein cholesterol ratio; Lymphocyte/high-density lipoprotein cholesterol ratio